Preparing for a New World of Work: Leadership Styles Reconfigured in the Digital Age - Laura BENCHEA; Anca Gabriela ILIE (European Journal of Interdisciplinary Studies)
As a consequence of the accelerated technological developments (artificial intelligence, robots, automation, quantum computing etc.) that humankind has developed over the latest decades, inquiries about the impact of these powerful technologies and digitalization over professional work have emerged in the business and academic spheres. Since digital transformation involves, among others, giving rise to new ways of sharing practical expertise and leading organizations, it has strong implications on leadership practice, in terms of new styles, skills, competences and other capabilities needed to implement this change and to successfully navigate organizations through the new wave of technological disruption. Against this backdrop, the aim of this paper is to identify patterns and trends across professions in general and how they were transformed by technology. In addition, the paper explores how executives prepare for the new world of work and which leadership styles are on the brink of fundamental change and are particularly relevant for the digital world.